Human Growth and Development - Beckett, Chris (SAGE Publications, Ltd. (UK), 2024)
Our bestselling social work textbook is back again. Taking you right back to basics, this book explains and analyses key theories in a really accessible way before going on to discuss, in detail, how theory can be incorporated into every day social work practice. Each chapter contains activities with step-by-step commentaries for discussion, self-analysis and critical reflection. The book very loosely follows the shape of a human life, beginning with a birth and ending with a death, but many of the chapters deal with ideas and topics that are relevant at many different stages of life, such as bereavement, attachment and learning. Its focus throughout is on psychosocial development – so psychological development within a social context – rather than physical development. This book is by Chris Beckett, a social work academic and novelist who previously worked in child and family social work, and Hilary Taylor, a psychotherapist and former social work academic who used to work in the field of social work with adults. It is the go-to guide for anyone studying for careers in the helping professions, such as nurses, social workers, occupational therapists, teachers and counsellors. It′s also supported by an online case study resource. Follow the lives of people living in the fictional London Borough of Bexford, with 12 extended case studies to help you explore key issues and themes raised in the book as well as develop the skill of linking theory to practice.